Structure and enzymatic degradation of the polysaccharide secreted by Nostoc commune. (May 2022) - Drouillard, Sophie; Poulet, Laurent; Marechal, Eric; Amato, Alberto; Buon, Laurine; Loiodice, Mélanie; Helbert, William
Abstract: Noctoc commune is a cyanobacterium living in various and extreme environments. Its ability to survive in desert, on ice or high altitude is explained by its exceptional metabolism and its capacity to resist to desiccation. N. commune cells are embedded in a gelatinous matrix made of polysaccharides which fixes water and participates in maintaining the cells in hydrated conditions. The structure of the polysaccharide of N. commune harvested in Saint Martin d'Uriage (France) and the oligosaccharides obtained after its enzymatic degradation were determined. The repeating unit of the main chain is a tetra-saccharide: [→4)-β-D-Glc p -(1 → 4)-β-D-Xyl p -(1 → 4)-β-D-Glc p -(1 → 4)-α-D-Gal p -(1→], branched at position 6 of a glucose residue by a β-linked pyruvated glucuronic acid residue. About 30% of the Xyl p residues were branched with a Xyl f residue. Comparison of this structure with the polysaccharides secreted by other Nostoc species and strains suggest a strong selection pressure on the structure in agreement with its important biological role. Graphical abstract: Image 1 Highlights: Purification of the polysaccharide secreted by Nostoc commune isolated in Saint Martin d'Uriage (France). Structure analyses of the polysaccharide and the oligosaccharides obtained by enzymatic degradation. The conserved N. commune polysaccharide structure isolated around in the world suggests a common biosynthetic template.